Chromosome size polymorphism in Plasmodium falciparum can involve deletions of the subtelomeric pPFrep20 sequence. - Patarapotikul, J (1988)
The P. falciparum pPFrep20 repetitive element from the Palo Alto Uganda strain has been isolated and sequenced. The Palo Alto pPFrep20 repeat (pPFPArep20) has a clustered subtelomeric location and on chromosome 1 has been deleted from one end. Analysis of chromosome 1 from 5 other strains has revealed that pPFrep20 sequences have been deleted from one end in 3 of them. Thus, deletion of pPFrep20 appears to be a frequent event that could significantly contribute to chromosome size polymorphism in P. falciparum.